2008
DOI: 10.1161/hypertensionaha.107.106690
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Related Difference in Arterial Elastance During Exercise in Patients With Hypertension

Abstract: Abstract-Exercise intolerance and heart failure with preserved ejection fraction are common in females. Recently, arterial stiffness has been suggested to be a significant contributor in the development of heart failure. How gender difference affects arterial stiffening and its response to exercise is not well known. We hypothesized that arterial elastance index during exercise would be more abnormal in females with hypertension than males. Arterial elastance index was estimated as arterial end systolic pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 22 publications
2
21
0
Order By: Relevance
“…Indeed when we separated our cohort into BP groups we find that ⌬E A I is associated with age and sex (data not shown). Further, Park et al (38) examined the change in E A I in the supine position and only reported data up to 75watts of exercise, which may further explain the differences between studies, as our figures show. E A I was originally derived from a 3-element Windkessel model which characterizes the hemodynamics of the arterial system as TACI, PVRI along with characteristic impedance (51).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Indeed when we separated our cohort into BP groups we find that ⌬E A I is associated with age and sex (data not shown). Further, Park et al (38) examined the change in E A I in the supine position and only reported data up to 75watts of exercise, which may further explain the differences between studies, as our figures show. E A I was originally derived from a 3-element Windkessel model which characterizes the hemodynamics of the arterial system as TACI, PVRI along with characteristic impedance (51).…”
Section: Discussionmentioning
confidence: 63%
“…In this study ⌬E A I was not associated with age or sex, which differs from previous studies. Park et al (38) found that older hypertensive women (59 Ϯ 8 yrs) expressed a greater change in E A I from rest to 75W compared with older (58 Ϯ 9 yrs) hypertensive men. Further, Najjar et al (34) found that during exercise E A I was similar in young and older normotensive men, but was higher in older vs. younger normotensive women.…”
Section: Discussionmentioning
confidence: 98%
“…[1][2][3][4] It can be explained by the change of female hormonal status and the loss of cardiovascular protection provided by estrogens in premenopausal women. [4][5][6] In addition, hypertensive females, even in the absence of large coronary artery disease and left ventricular systolic dysfunction, tend to experience more symptoms related to AH, including impaired exercise tolerance and chest pain. 6 Although women with AH are more aware of the need of treatment and visit physicians more frequently 2 they do not reach satisfactory control of BP.…”
Section: Introductionmentioning
confidence: 99%
“…These parameters can be measured noninvasively. 9,[18][19][20] In this study, we found these indices of afterload were closely related to the ventricular diastolic functional indices at various exercise stages. Interestingly, despite no significant differences in the systemic vascular resistance index between the 3 groups, total arterial compliance and the pulsatile component of afterload significantly differed, thereby leading to differences in Ea.…”
Section: Ventriculoarterial Interactionmentioning
confidence: 50%
“…Several studies also used noninvasively measured Ea during exercise. 18,22,23 Furthermore, we think that the main result of our study, which is that the resting VVI can predict exercise capacity, might not be significantly affected by this limitation. Future study should validate Doppler-derived Ees during exercise.…”
Section: Study Limitationsmentioning
confidence: 76%